Phytochemical profiling and biological evaluation of Annona muricata L. root extract: A comprehensive assessment - Gama, M M G; Rani, K R B (Plant Science Today, 2025)
Annona muricata Linn., a component of the Annonaceae family, is a fruit-bearing tree endowed with a rich tradition of utilization. Recognized by various colloquial names such as soursop, graviola, and guanabana, Annona muricata is an evergreen botanical species predominantly found in tropical and subtropical zones globally. The current study was designed to evaluate the antioxidant and antibacterial properties while simultaneously elucidating the quantitative composition of phytochemical constituents within the root extract responsible for the pharmacological activities of the investigated subject. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) method was used to assess antioxidant activities, while the well diffusion method evaluated antibacterial activity against common pathogens. Researchers have reported various bioactive compounds alkaloids, phenols, etc., that exhibit antibacterial, antifungal, antitubercular, anticancer, antioxidant, and other prophylactic activities. The chloroform extract displayed notable inhibitory efficacy against E. coli MTCC 443, indicating increased susceptibility with a minimum inhibitory concentration (MIC) of 0.3 mg/mL. The sample exhibited a comparatively elevated alkaloid content compared to its phenolic content. Bioactive phytoconstituents with diverse biological activities, justifying the rationale for their therapeutic use by local inhabitants.